Pittsburgh sleep quality index for use in cardiopulmonary and metabolic rehabilitation Índice da qualidade do sono de pittsburgh para uso na reabilitação cardiopulmonar e metabólica Índice de calidad del sueño de pittsburgh para uso en la rehabilitación cardiopulmonar y metabólica - de Araujo P.A.B.* (2015)
© 2015, Redprint Editora Ltda. All rights reserved.Introduction: Sleep quality is a relevant parameter in the assessment of overall health, and a relevant factor in determining the risk of cardiovascular diseases. Objective: To validate the adapted version of the Pittsburgh Sleep Quality Index (PSQI) for use in cardiopulmonary and metabolic rehabilitation (CPMR) programs. Methods: Descriptive cross-sectional study conducted with 101 patients of both sexes, average age of 66.05 (± 13.9) years. For statistical analysis, it was considered a confidence interval of 95% and significance value of p <0.05; for internal consistency analysis the Cronbach’s alpha was used and for analysis of the relationship among components and items and the total score of the questionnaire the Spearman correlation was used. Results: All components of the questionnaire showed good internal consistency with a value of 0.72. The components that most closely related to the total score were “duration of sleep” and “subjective quality of sleep”, and the least related was “sleep changes”. Among the items, the variation was 0.584 in item “during the last week, in general, how would you rate the quality of your sleep?”, until -0.611 in item “during the last week, how many hours could you sleep at night? “. We could observe that the items “cough or snore too high” and “frequency of sleep difficulties for other reasons” were not correlated with the total score of the questionnaire. Conclusion: The adapted PSQI version is valid for use in sleep assessment in CPMR programs.